Validity test of POCT (Point of Care Testing) method on blood glucose examination using whole blood samples, serum, and EDTA plasma - Kafesa, Ally; Noviyanti, Santi; Nurdin, Nurdin; Sutomi, Muhammad Alwi (Lighthouse Publishing, 2022)
Medical laboratory services can support disease diagnosis or monitor patient recovery. The reality of the POCT method has been widely used by clinical laboratories. The tool is not only used for screening but is also used to check the diagnosis of diabetes mellitus. This research aims to determine the validity of the POCT method on whole blood, serum, and plasma EDTA samples on blood glucose tests. The research method of this study used the descriptive-analytical method using the POCT method on blood glucose tests using three different types of samples, whole blood, serum, and plasma EDTA. Precision tests were accepted on normal and pathological serum samples with CV% of 2.02% and 2.27%. The accuracy test was accepted on a normal and pathological serum with TE% values ​​of 8.54% and 6.03%. The linearity test is accepted on serum–plasma EDTA samples with an r2 value of 0.998. The sigma values ​​are in the unacceptable area. The use of the POCT tool for blood glucose examination has a valid performance value. The deviation of the examination results is influenced by pre-analytical errors such as sampling and processing samples so that the total error obtained is higher than the total allowed error. The POCT tool can be used for all types of samples.